Thermal oxidation of steel mesh for water-oil separation process. (2022) - Hardinah, Tri; Muhammad, Rayi; Ismardi, Abrar; Pangaribuan, Porman; Lockman, Zainovia; Budiman, Faisal
Abstract: Thermal oxidation of steel mesh has been performed to form oxide nanostructure and used as membrane for water-oil separation. Oxidation at high temperature provides nanostructures growth, and the oxidized steel mesh also serves hydrophobic and semi-permeable property: it repels water but infiltrates oil, which beneficial for separation of oily water. After successfully fabricating the semi-permeable membrane, the membrane was attached to a designated device. The performance of the oxidized mesh for water-oil separation process then was assessed in the designated device with series of oily water experiments and experimental results showed that the membrane could separate the oily water, with separation efficiency reaching ∼90%, for 30 ml initial oil volume. Moreover, the oxidized steel mesh membrane also provided excellent repeatability and consistent separation efficiency. It is of interest to investigate it further since it offers easy and inexpensive technology to separate water and oil and solving oil pollution problem.